Ceramic microspheres to improve anticorrosive performance of phosphate paints - Deya, Marta Cecilia (2012)
Zinc phosphate and related compounds have been proposed as "green" replacements for traditional anticorrosive pigments such as zinc chromate and lead oxides. However, environmental concerns have risen in the last years because the disposal of these materials in the environment increased phosphate levels in water and produce eutrophication of water bodies. The present paper deals with the possible incorporation of ceramic microspheres in alkyd paints in order to diminish phosphate content. The results suggested that paints with low phosphate content can be successfully formulated with a suitable selection of the amount and type of microspheres.